Quality monitoring, collusion and sub-contracting - Michael Kuhn; Qianhui Yan (Universität Rostock, Institut für Volkswirtschaftslehre, 2006)
We discuss the social welfare improvement under centralized and decentralized hierarchies and focus on supervisoris ability to monitor quality. Although the possibility of collusion against the principal is eliminated under decentralized hierarchy, the decentralization is dominating only if supervisory accuracy is large enough in the case of public information. Private information about the accuracy hurts the principal under both hierarchies. The optimal effort in hierarchy A is pooling one. The dominance of decentralization over centralization depend combination of accuracies of both the low and the high type supervisor.
Keywords: D73; D82; I18; L22; 330; auditing; collusion; delegation; hierarchy; quality